Zur Frage des Anwachsens mehrdeutiger Lösungen gewöhnlicher Differentialgleichungen erster und zweiter Ordnung - Streliz, S. (Lithuanian Mathematical Journal, 1961)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Ш. Стрелиц. К вопросу о росте неоднозначных решений обыкновенных дифференциальных уравнений Š. Strelicas. Pirmos ir antros eilės paprastųjų diferencialinių lygčių nevienareikšmių sprendinių augimo klausimu